Challenges and Choices Amidst Military Conflict: The Present and Future of Medical Education and Healthcare in Sudan - Sohaib Mohammed Mokhtar Ahmed; Mohanned Bushra Masaad; Mohamed Salah Abdulrazeg Abdulrahman; Elnazeir Mohamed Ibrahim Mohamedzain (Health Science Reports)
ABSTRACT Background The situation for medical education and healthcare in Sudan has been challenging for the recent years, and emigration of physicians is an ongoing problem threatening the healthcare system. We conducted this study to understand the future plans of medical students and their perceptions regarding their medical education and healthcare system. Method We performed this cross‐sectional study at five public and private Sudanese medical schools in November 2023. We distributed the questionnaire electronically through an Online Google Form via social media platforms, such as WhatsApp Messenger. Descriptive statistics were employed for the data analyses. Results The mean age (±SD) of the students was 22.2 (±2.7) years, and females constituted 61.8% (397) of the study sample. About 18% of the students rated their medical training as excellent, and half of them (50%) said that it was good. Nearly half of the students believed the quality of healthcare services in hospitals was poor (46%) along with a shortage or severe shortage in its number (49%). A majority (58.4%) thought frequently or constantly about leaving Sudan after graduation. Reasons given for leaving included better personal lifestyle, avoiding conflict, advanced training, and better professional opportunities and salary. Leading motives for staying included the pull of friends and family and a sense of responsibility to the country. Conclusion This study indicated the pressing need for comprehensive interventions to address the challenges faced by medical students in Sudan. The strong desire to emigrate increased by the current conflict, coupled with concerns about the healthcare system and medical education, poses a significant threat to the future of healthcare services in the region.